Organizational Culture and HR Management in Public Sector: Social Exchange Mechanisms in the Merit System for Senior Official Selection in Riau Provincial Government - Ikhwan Ridwan; Oman Sukmana; Rachmad Kristiono Dwi Susilo; Junaidi Junaidi (Yayasan Darussalam Bengkulu, 2026)
Background: Organizational culture and HR management in public bureaucracy face a structural paradox when formal merit systems operate alongside deeply embedded socio-cultural norms. Riau Province's Civil Service Merit Index rose from 227.5 (2019) to 325.5 (2024), yet the